MEDIA EDUKASI BERBASIS PERTANIAN INDUSTRIAL MENINGKATKAN HASIL BELAJAR SISWA MATERI KEGIATAN EKONOMI - Wahyuni, Vivi; Himmah, Elok Faiqotul; Yuntari, Dwi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
This study aims to explore the use of educational media based on industrialagriculture using Android applications to improve student learning outcomes inlearning economic activities in class IV SDN Jarit 01. This study uses quantitativeresearch with an experimental approach. The research participants consisted of 23fourth grade students from SDN Jarit 01. Data collection was carried out throughtests that produced numbers and statistics. The collected data were analyzed withdescriptive analysis techniques, where this technique is used to provide an overview of the collected data. Descriptive analysis involves statistical calculations such as mean (average), median (middle value), and standard deviation to describe the characteristics and variations of the data. From the data that has been analyzed through pretest and posttest scores, there is a very significant value in student learning outcomes after using Android-based educational media. In the pretest value (before using android-based educational media), students obtained an average of 68.9130, and after using educational media, student learning outcomes became 80.00. Referring to the analysis of learning outcomes proves that there is a significant influence between the use of media and student learning outcomes. The conclusion of the research results shows that the use of educational media based on industrial agriculture through Android applications contributes to improving student learning outcomes in terms of understanding concepts related to economic activities.